A modified lm=1 stellarator magnetic system - Kotenko, V.G. (Вопросы атомной науки и техники, 2011)
Numerical studies into the toroidal magnetic field structure of a new modification of the l=1 polarity stellarator with a single (m=1) helical coil pitch along the whole length of the torus have been undertaken. Depending on mutual toroidal and helical magnetic field directions, there may exist two centered magnetic surface/helical divertor configurations in the modified lm=1 stellarator. Similar helical divertor configurations have been realized in the tokamak [9, 10] in order to stabilize large-scale instabilities and to avoid current disruption.